Huanglongbing (HLB; citrus greening) and Nutrient Deficiency Identification - Tripti Vashisth; Megan M. Dewdney; Jamie D. Burrow (EDIS)
Huanglongbing (HLB) is a bacterial disease that is spread by an insect, the Asian citrus psyllid. This 2-page fact sheet explains how to tell the difference between HLB symptoms and symptoms from nutrient deficiencies. Written by T. Vashisth, M.M. Dewdney, and J.D. Burrow, and published by the Plant Pathology Department, June 2016.